INFLUENCE OF SCATTERED NEUTRON RADIATION ON METROLOGICAL CHARACTERISTICS OF АТ140 NEUTRON CALIBRATION FACILITY - D. I. Komar; S. A. Kutsen (Приборы и методы измерений, 2017)
Today facilities with collimated radiation field are widely used as reference in metrological support of devices for neutron radiation measurement. Neutron fields formed by radionuclide neutron sources. The aim of this research was to study characteristics of experimentally realized neutron fields geometries on АТ140 Neutron Calibration Facility using Monte Carlo method.For calibration, we put a device into neutron field with known flux density or ambient equivalent dose rate. We can form neutron beam from radionuclide fast-neutron source in different geometries. In containercollimator of АТ140 Neutron Calibration Facility we can install special inserts to gather fast-neutron geometry or thermal-neutron geometry. We need to consider neutron scattering from air and room’s walls. We can conduct measurements of neutron field characteristics in several points and get the other using Monte Carlo method.Thermal neutron collimator forms a beam from radionuclide source with a significant amount of neutrons with thermal energies. From found relationship between full neutron flux and distance to neutron source we see that inverse square law is violated. Scattered radiation contribution into total flux increases when we are moving away from neutron source and significantly influences neutron fields characteristics. While source is exposed in shadow-cone geometry neutron specter has pronounced thermal component from wall scattering.In this work, we examined main geometry types used to acquire reference neutron radiation using radionuclide sources. We developed Monte Carlo model for 238Pu-Be neutron source and АТ140 Neutron Calibration Facility’s container-collimator. We have shown the most significant neutron energy distribution factor to be scattered radiation from room’s walls. It leads to significant changes of neutron radiation specter at a distance from the source. When planning location, and installing the facility we should consider radiation quality requirements.